Implementation of Ticket Sanctions for Traffic Violations Based on Law No. 22 of 2009 at the Sorong City Police Traffic Unit - Ferderika Massa; Muharuddin Muharuddin; Sokhib Naim (Faculty of Law, Universitas Muhammadiyah Sorong, 2024)
Traffic violations are one type of offense that is included in certain criminal offenses. In the context of Indonesian law, every offense, whether it is a crime or a violation, must be processed in accordance with the applicable laws. However, there are still many students and people who commit violations such as driving without a driver's license, STNK, violating red lights, and not wearing a helmet. Although the police are responsible for traffic order, often the settlement of violations is not in accordance with the provisions of the law, even settled on the spot by unscrupulous law enforcement officers. Traffic law should create order and freedom for society, by combining the freedom of road users with order. This research aims to explore the application of ticket sanctions against traffic violations based on Law No. 22 of 2009 concerning Road Traffic and Transportation at the Sorong City Police Traffic Unit. The research method used is empirical juridical with descriptive analysis approach. The results showed that the application of ticket sanctions against traffic violations includes various types of sanctions in accordance with the violations committed, such as principal and additional punishment. The application of ticket sanctions is carried out through various stages, including written legal action using ticket stamps. In addition, the research also revealed that minors who commit traffic offenses are enforced with special considerations, taking into account the truth, justice, and welfare of the child. This research underscores the importance of road traffic and transportation in supporting national development and integration, as well as the need to develop its potential and role in realizing traffic safety and order.